Pre-term labor screening evaluation of the results after passing through the day hospital - Dias de Araújo, Fernanda; Acosta, Estela Mercedes (SCT Proceedings in Interdisciplinary Insights and Innovations, 2023)
Background: Preterm birth (PTP) is one of the most frequent complications in maternal-fetal medicine. It is the leading cause of neonatal morbidity and mortality, which will be inversely proportional to the age at delivery. PPA is characterised by regular contractions and cervical changes in pregnant women from 22 weeks to 36.6 weeks with whole amniotic membranes. If treatment fails, it leads to preterm labour. There are different risk factors, primigravidae, socio-economic factors, environmental factors, drug and alcohol consumption, intrauterine growth restriction, pre-eclampsia, maternal weight and height, multiple pregnancies, infections, previous preterm births for example. Primigravidae are the most frequent to have a preterm birth, although it has been shown that multiparous women with risk factors, previous preterm birth and others also cause preterm birth. Material and methods: A study will be made of the medical records of all the pregnant women who passed through the day hospital in 2018, and an assessment will be made of how and at what gestational age their deliveries were carried out, as well as how they benefited from having been attended at the Ana Goitia Maternal and Children’s Day Hospital. In addition to their medical records, hospital records such as the delivery book and bibliographic and academic scientific articles from PubMed and Google Scholar were used. Those whose pregnancies were not found to be terminated were excluded. Results: A retrospective study was carried out in 2018 and half of 2019, of all pregnant women with threatened preterm labor or with risk factors, admitted to the Hospital Especializado Materno Infantil de Agudos Ana Goitia. Conclusion: It was observed that the use of the Protocol implemented in August 2012, in the Ana Goitia Specialised Maternal and Child Acute Hospital, was positive compared to years in which the Protocol was not yet in force, as most of the pregnant women with threatened pre-term labor or risk factors, had successful pregnancies